Pembuatan Aplikasi Sistem Administrasi Toko Aditya Motor Surabaya - Andrew Agatha; Justinus Andjarwirawan; Lily Puspa Dewi (Jurnal Infra, 2018)
Aditya Store is a store that sell motorcycle sparepart and provide motorcycle service at affordable price. This store located at strategic location and have many customers. However, while writing record of sales record, purchase record, inventory record and etc, this store still using old way where that way still has many weakness. Some problems come up, like, lost items or calculation of profit and loss store sometimes give wrong result (human error). From that background, the owner of the store wants to change over using administrasion system in IT which is neatly structured, so the system can support Aditya Store’s performance while making sales, purchases, sales return, bookkeeping, account receivable and etc. This administration sistem is created using programming languange PHP (Hypertext Preprocessor), HTML (Hyper Text Markup Language), MYSQL as database and Laravel 5 as Framework. Result obtained from this application such as there are master recording, sales and purchases record that structured and computerized equipped with stoked card with average method and financial report profit and loss in Toko Aditya Motor.